The contribution of strategic environmental assessment to transport policy governance - Rodrigo Jiliberto Herrera (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
At the turn of the new millennium, therefore, the initial work on SEA (Strategic Environmental Assessment) and transport are eliciting work to evaluate the interest, specifics and feasibility of applying this new tool when formulating transport policy; and a positive appreciation is consolidating of its use and relevance as a tool to support decision-making in this sector. This initial positive assessment is responsible for increasing use of SEA in the design of transport plans and programmes, and a wide ranging analytical toolkit has been developed to adapt to the specifics of the relation between transport planning and the environment - in terms of its main environmental effects, the scales of planning work, the diversity of planning models and the typology of strategic transport decisions. Rather than considering the singularity or specific nature of SEA as applied to decision-making on transport policy, subsequent developments have sought to facilitate and promote the use of this tool by disseminating specific cases or producing guides. This relatively strong development of SEA in the transport sector does not, however, mean that it is free from controversy and ambiguities, because, as shown in the literature (Dalal-Clayton and Sadler, 2005) and by the international SEA community (Wallington et al, 2007, 2008), there is still an ongoing debate on key aspects of SEA, including the definition of its basic objectives.
Keywords: 330